Diagnosis of Swimming Induced Pulmonary Edema—A Review - Hannes Grünig (Frontiers in Physiology, 2017)
Swimming induced pulmonary edema (SIPE) is a complication that can occur during exercise with the possibility of misdiagnosis and can quickly become life threatening; however, medical literature infrequently describes SIPE. Therefore, the aim of this review was to analyse all individual cases diagnosed with SIPE as reported in scientific sources, with an emphasis on the diagnostic pathways and the key facts resulting in its diagnosis. Due to a multifactorial and complicated pathophysiology, the diagnosis could be difficult. Based on the actual literature, we try to point out important findings regarding history, conditions, clinical findings, and diagnostic testing helping to confirm the diagnosis of SIPE. Thirty-eight cases from seventeen articles reporting the diagnosis of SIPE were selected. We found remarkable differences in the individual described diagnostic pathways. A total of 100% of the cases suffered from an acute onset of breathing problems, occasionally accompanied by hemoptysis. A total of 73% showed initial hypoxemia. In most of the cases (89%), an initial chest X-Ray or chest CT was available, of which one-third (71%) showed radiological signs of pulmonary edema. The majority of the cases (82%) experienced a rapid resolution of symptoms within 48 h, the diagnostic hallmark of SIPE. Due to a foreseeable increase in participation in swimming competitions and endurance competitions with a swimming component, diagnosis of SIPE will be important, especially for medical teams caring for these athletes.